Difference oxytocin massage and endorphin massage against reduction in pain scale during first stage of labor - Muji Iriana; Nor Asiyah; Nasriyah Nasriyah (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Oxytocin massage is a massage along the spine to stimulate an increase in oxytocin, which serves to increase uterine contractions, promote relaxation, and reduce pain perception. Meanwhile, endorphin massage is performed with gentle massage on the back, shoulders, and arms to stimulate the production of endorphins as the body's natural analgesic. Both methods have been proven to help reduce pain, but their relative effectiveness varies, so further study is needed. Purpose: To determine the difference in effectiveness between oxytocin massage and endorphin massage on reducing the pain scale during the first stage of labour. Method: This study used a quasi-experimental design with a two-group pretest–posttest approach. A sample of 40 mothers in labour was selected using purposive sampling and divided into two groups, namely the oxytocin massage group and the endorphin massage group. Pain was measured using a Numeric Rating Scale (NRS) before and after the intervention. Data analysis was performed using the Shapiro–Wilk normality test, followed by Wilcoxon and Mann–Whitney tests for intergroup comparisons. Results: The results of the study showed that there was a significant difference in pain scale before and after oxytocin massage, with a p-value of 0.000. There was a significant difference in pain scale before and after endorphin massage, with a Wilcoxon test p-value of 0.000. Conclusion: There was no significant difference between oxytocin massage and endorphin massage in reducing the labour pain scale at RA Kartini Regional General Hospital in Jepara, with a Mann-Whitney p-value of 0.289. Suggestion: Other researchers are advised to develop additional variables such as anxiety levels and duration of labour, and to compare other non-pharmacological interventions in order to obtain different results.